Consequências do estresse de derrota social (episódico e contínuo) sobre os efeitos psicomotores e reforçadores condicionados da nicotina em camundongos - Domingues, Liz Paola [UNIFESP] (2016)
Objective: This study aimed to investigate the consequences of two types of repeated social defeat stress (episodic and continuous) on nicotine-induced psychomotor effects and conditioned reward in mice. Methods: Using the resident-intruder model, experimental mice (intruder) were defeated by an aggressive one (resident). After each daily defeat, intruders returned to their homecage (episodic stress) or cohabitated with the aggressor for 24h (continuous stress), until the next defeat. After the 10-day stress protocol, different batches of mice received nicotine (0.1 mg/kg, s.c.) in locomotor tests (short- and long-term), or for conditioned place preference (CPP). Results: Both defeat protocols induced short-term (within 24h) locomotor suppression, which was potentiated by nicotine only after continuous defeat stress. Ten days after the final defeat, locomotor suppression was no longer observed due to stress or nicotine. Nicotine failed to induce place preference or aversion after either defeat protocol. Only the episodic defeat group showed nicotine-induced locomotor suppression one week after the additional nicotine exposure during the CPP protocol. Conclusion: Our findings indicate that different consequences of episodic and continuous stress on nicotine psychomotor effects were observed shortly after stress. Differential long-term effects on nicotine locomotor response were only observed when stressed mice were further exposed to repeated nicotine administration (during CPP). Also, neither episodic nor continuous defeat stress facilitated the acquisition of conditioned place preference or aversion to nicotine.